Dynamic simulation of bistable electrofluidic device based on a combined design of electrode and wettability patterning. Issue 1 (14th March 2018) - Zhao, Qing; Tang, Biao; Bai, Pengfei; Zhou, Rui; Li, Hui; Li, Fahong; Groenewold, Jan; Zhou, Guofu
Abstract: Electrowetting has shown its power in manipulating microfluidics. Of particular interest is a bistable electrowetting system, which enables versatile low power consumption applications. A combined design of electrode and wettability patterning, which includes a unique three‐electrode structure and wettability barrier, was proposed and introduced into as a new electrofluidic display (EFD) architecture. This architecture should be manufacturable in a fairly straightforward way within LCD cell‐making technology. For this architecture, an electrohydrodynamic two phase flow simulation was carried out using the COMSOL Multiphysics simulation software. The results show that this new EFD architecture could achieve a bistable display property. Compared with conventional EFD, the electro‐optical performance (the aspect ratio and response time) of this design has also been greatly improved. Abstract : We report a new bistable electrofluidic display (EFD) pixel structure that enables versatile low‐power applications.The fluid dynamic behavior within a pixel of a bistable EFD based on a combined design of electrode and wettability patterning is thoroughly investigated through an electrohydrodynamic simulation.The results show that the bistable electrofluidic device can greatly improve the electro‐optical performance of EFD device.